Effect of Theory-Based Training Intervention on Physical Activity and Blood Pressure in Hypertensive Patients a Randomized Control Trial: A Literature Review - Destia Widyarani (Lembaga Penelitian dan Pengabdian Masyarakat Program Studi DIII Keperawatan Universitas Bondowoso, 2020)
Introduction: Hypertension is a disease that is a serious health problem in society, this is due to the high number of morbidity and mortality due to hypertension each year. Hypertension is the third leading cause of death worldwide, with 7.5 million deaths annually (12.8% of all deaths). Prevention that can be done to avoid complications due to hypertension according to the Sevent Report of the Joint National Committee (JNC 7) is lifestyle modification. Method: method of calculating the sample clearly has been explained, namely that after obtaining the number of sample populations, the respondents were divided into the treatment group and the control group (39 people each). In each group, the initial systolic blood pressure was measured, with the mean systolic blood pressure for the treatment group Result: Measurements were made with a brisk 30 minute walk with an intensity value of 40% -60% of the maximum reserve heart rate. The determination of outcome measures was carried out twice, namely the first before intervention and the second measurement after the intervention for three months. Some of the components measured are exercise self-efficacy (ESE), healthy behavior, physical activity, intensity of walking, and 24 hours of ambulatory blood pressure (ABP). Conclusion: One of the usual lifestyle modifications is aerobic or physical activity such as walking fast (at least 30 minutes most days of the week). To form healthy behavior in hypertensive patients, it is necessary to apply a theory that helps in understanding the importance of lifestyle modification in hypertensive patients.